Acupuncture combined with moxibustion promote the recovery of spinal cord injury in correlation with Shh/Gli-1 signaling pathway. (2nd January 2022) - Ding, Li-Li-Qiang; Hu, Song-Feng; He, Xing-Wei; Zhang, Peng; Zhao, Fen-Fen; Liu, Ting-Ping; Zhang, Qin; He, Fan; Yu, Ying; Xiong, Peng; Wang, Chang-Kang
Abstract : Objective: Acupuncture combined with moxibustion (AM) therapy has been applied to treat spinal cord injury (SCI), but the underlying mechanism is unclear. The present study aimed to confirm the effect and mechanism of AM treatment on the recovery of SCI. Design: Male Sprague–Dawley rats were used to establish the SCI model by impact method. SCI rat models were subjected to AM treatment at Dazhui (GV14) and Jiaji points (T7-T12), Yaoyangguan (GV3), Zusanli (ST36) and Ciliao (BL32). Outcome measures: Motor function and cell apoptosis in rats after SCI. The mRNA and protein expression levels of Shh and Gli-1 were determined by real-time quantitative polymerase chain reaction, western blot and immunohistochemistry. Results: After AM treatment, the hindlimb motor function of SCI rats was significantly increased than the SCI group at 7, 9, 11, 14 days (P < 0.05). AM treatment 7 d and 14 d significantly preserved the nissl-stained positive neurons and significantly decreased number of apoptotic cells, compared to that of SCI 7 and 14 d groups (P < 0.05). AM treatment improved the mRNA protein levels of Shh and Gli-1 after 7 and 14 days treatment compared to the SCI group (P < 0.05). Conclusion: AM could improve the expression of Shh and Gli-1 in injured spinal cord of rats. That could be part of underlying mechanisms of AM treatment including recover motor function and preserve the neuron cells and alleviate the apoptosis of nerve cells in rats after SCI.